Rupture of intermetallic networks and strain localization in cast AlSi12Ni alloy: 2D and 3D characterization. (15th June 2016) - Tireira, A.; Requena, G.; Sao Jao, S.; Borbely, A.; Klocker, H.
Abstract: Damage development during tensile straining of a cast AlSi12Ni alloy has been characterized by in situ SEM imaging and synchrotron X-ray microtomography. Two main damage mechanisms consisting of intermetallic particle rupture and decohesion of Al-Si interfaces were revealed. Particle rupture takes place already from the beginning of the deformation, while decohesion of Al-Si interfaces is more characteristic at later stages. It is shown that damage evolution in the alloy is closely related to the underlying geometry of the intermetallic phase, its clustered structure playing a double role in controlling strain localization in the matrix as well as the rupture sequence of the intermetallic phase itself. The latter shows that small clusters break-off from the complex intermetallic network before large clusters, in good agreement with their load carrying capacity determined by the local volume fraction of the intermetallic phase. Finite element modeling of the alloy's tensile behavior evidences that deformation bands formed in the alloy with complex structure are similar to those developed in a model particle reinforced metal-matrix composite, where the particles correspond to the clustered regions of the intermetallic phase. Graphical abstract: